2017
DOI: 10.1090/bull/1592
|View full text |Cite
|
Sign up to set email alerts
|

Black hole formation and stability: A mathematical investigation

Abstract: Abstract. The dynamics of the Einstein equations feature the formation of black holes. These are related to the presence of trapped surfaces in the spacetime manifold. The mathematical study of these phenomena has gained momentum since D. Christodoulou's breakthrough result proving that, in the regime of pure general relativity, trapped surfaces form through the focusing of gravitational waves. (The latter were observed for the first time in 2015 by Advanced LIGO.) The proof combines new ideas from geometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In [9] we have shown that this solution is, although singular, still surprisingly well-behaved in a way that it satisfies the second Bianchi identity weakly. The stability of this solution may be studied using metric convergence, e.g., in the sense of Gromov-Hausdorff convergence or Sormani-Wenger intrinsic flat convergence [1,6,22,29,30].…”
Section: Construction Of Admissible Initial Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In [9] we have shown that this solution is, although singular, still surprisingly well-behaved in a way that it satisfies the second Bianchi identity weakly. The stability of this solution may be studied using metric convergence, e.g., in the sense of Gromov-Hausdorff convergence or Sormani-Wenger intrinsic flat convergence [1,6,22,29,30].…”
Section: Construction Of Admissible Initial Datamentioning
confidence: 99%
“…We briefly examine how this was achieved for certain matter models. We will not discuss the vacuum case here, as it differs significantly from the treatment for matter models (spherically symmetry cannot be employed due to Birkhoff's Theorem) and an excellent review has already been written by Bieri [6].…”
Section: Introductionmentioning
confidence: 99%
“…Footnote 11 (continued) but "infinitely extended") for Reissner-Nordström and Kerr. The pde approach to gr, on the other hand, is based on two slogans, appealing to the fundamental theorem of Choquet-Bruhat and Geroch [29]: 12 • All valid assumptions are about initial data;…”
mentioning
confidence: 99%
“…13 Finally, an Appendix written by Erik Curiel traces the definitional history of the concept of a black hole. 12 A Cauchy surface in a space-time (M, g) is a subset Σ ⊂ M such that each endless timelike curve intersects Σ exactly once. This makes Σ a closed connected 3d submanifold of M which can be chosen space-like and hence Riemannian.…”
mentioning
confidence: 99%
See 1 more Smart Citation